Motivation and Attitudes of Indonesian Mechanical Engineering Students towards Learning English - Retnowaty Retnowaty (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. Motivation and attitudes are important factors in learning English effectively. The purpose of this study is to investigate the motivations and attitudes of Indonesian mechanical engineering students regarding English learning. This is a qualitative research method which used an online platform questionnaire survey to collect data. Participants in this study included 25 mechanical engineering students from Balikpapan University in Indonesia. The data was analyzed by categorizing quantitative data derived from questionnaires based on frequency of distribution. The findings revealed that Indonesian mechanical students in engineering were enthusiastic about learning English and had a positive attitude toward it. Furthermore, the results show that the participants placed a greater emphasis on instrumental motivation for learning English. It is indicated that they would like to participate in training sessions to increase their ability to match instrumental motivation. This study's findings confirmed that attitude and motivation were important factors in learning English. As a result, teachers and lecturers must work hard to increase motivation and positive feelings toward English language learning. This study may assist teachers in improving their classroom preparation by gaining a better grasp of their students' attitudes and simplifying learning activities for them. Furthermore, the findings of this study may help authorities and policymakers understand the importance of students' attitudes in developing ESP education policies, creating curriculum, and developing materials for ESP students.Keywords: Motivation, Attitudes, Mechanical Engineering Students, Learning English, ESP